Adolescent health and sex education at school: weavings from students' perspectives (Research, Society and Development, 2020)
This study aims to research the understanding of students about the importance of approaching the theme "Adolescent Health" in the school space and to investigate their knowledge about Sexual Education. It also presents the results of a dynamic developed with students on these two issues. The qualitative research was carried with students from an elementary public school in southern Brazil. As a data collection instrument, a questionnaire was applied, and the data collected was analyzed using the “Content Analysis” technique. A group dynamic was related to the adolescent health and the sexual education thematic subjects. Results indicated that the students recognize the importance of the school as a promoter of the adolescent health theme. Most students said to have knowledge about sex education. However, the knowledge cited by the students is more related to biological issues, without having a more comprehensive sex education dimension, such as gender relations, interpersonal relationships, body senses and self-esteem. School was cited by the students as the main source of information about sex education. During the group dynamics, it was possible to perceive the students' interest in participating in activities that address questions about health and sex education. It is concluded that the school is a significant space for the problematization on this theme. Furthermore, it is imperative to develop school-based sex education strategies that meet the needs of the students, in a personalized, human and qualified way, considering social, cultural and emotional aspects of the students.